STRATEGI KOMUNIKASI BNN PROVINSI RIAU DALAM PENCEGAHAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOBA (P4GN) - HOTMAULINA MARIA BR. HALOHO; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The problem of abuse and illicit drug in many countries has become a crucial issue, including Indonesia. In Indonesia, Riau particular is an area of central western region of Indonesia that has many entrances from the outside, the year 2012 recorded the BNN of Riau drug users reached 2% and if not minimized projected in 2015 will reach 2.12%. As concrete steps to stem the abuse and illicit drug the government launched a program P4GN 2011-2015 BNN stage to make 97.2% of the Indonesian population immune to abuse and illicit drug and 2.8% of Indonesia's population (drug abuser) gradually gets medical rehabilitation services and social rehabilitation. BNN of Riau implement programs P4GN to achieve the "Riau Drug-Free Year 2015", to achieve this goal BNN of Riau require communication strategy. This study aims to determine the communication strategy BNN of Riau in Prevention, Combating Drug Abuse and Illicit Drugs (P4GN) and to determine the constraints BNN of Riau in the Prevention, Combating Drug Abuse and Illicit Drugs (P4GN).This study used qualitative research methods with a presentation of descriptive analysis is to illustrate and describe the state of the subject or the object of research, at the present time based on the facts that appear. This study uses a model interactive data analysis of Hubermen and Miles, using the technique of checking the validity of the data the extension of participation and triangulation.The results of this study showed that the communication strategy BNN of Riau preformance Prevention, Combating Drug Abuse and Illicit Drugs (P4GN) with four factors, identify target communications, media selection, message communication assessment purposes, the role of communicators in the communication. In implementing the P4GN, BNN of Riau have problems of various factors, community participation, lack of quantity of personnel and lack of coordination among agencies).Keywords : communication strategy,drug, BNN of Riau, P4GN